Tarawangsa Traditional Music: An Ethnomusicological Study in Sukaluyu Village, Girimukti Village, Sumedang - Supriatna, Nanang; Sukmayadi, Yudi; Purwanto, Andrian (Universitas Negeri Semarang, 2025)
Tarawangsa traditional music in Sukaluyu Village, Sumedang Regency, has undergone a significant transformation due to the community’s social, cultural, and religious dynamics. Once a sacred function in the Bubur Sura ritual that contains elements of belief in Dewi Sri and ancestors, this art has now shifted to become a medium for entertainment, therapy, and public performances. This study aims to examine the changing function of Tarawangsa in the context of contemporary Sukaluyu society. The method used is qualitative-descriptive, with data collection techniques through participatory observation and in-depth interviews with artists and local communities. The results showed that shifts in community values, the influence of globalization, and changes in religious orientation have led to the cessation of the main ritual practice since 2018. Nevertheless, Tarawangsa has survived through thanksgiving performances, healing ceremonies, and cultural activities in local media and art festivals. These findings confirm that Tarawangsa is a dynamic and adaptive cultural heritage, with strong preservation potential when managed in a contextual and participatory manner.